Bio-inspired laminated graphite nanosheets/copper composites. Issue 63 (10th July 2015) - Wang, P.; Liu, W.; Chen, L.; Mu, C.; Qi, G.; Bian, F.
<x xml:space="preserve">Abstract</x> Bio-inspired laminated graphite nanosheets/copper composites with modified mechanical properties.